PENGARUH KETERLIBATAN KARYAWAN TERHADAP KINERJA KARYAWAN DI SMK NEGERI 1 SANGATTA UTARA - Paridah , Paridah; Darajat, Sakia; Sakka, Herlina; Azainil , Azainil (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to determine whether there is an influence of employee engagement on employee performance at SMKN 1 Sangatta Utara. The number of samples in this study was 68 employees. The data for this study were collected through the distribution of questionnaires to respondents, and then analyzed using a linear regression approach. Based on the results of testing with SPSS between employee engagement (X1) and employee performance (Y), the calculated t was 17.581> t table 2.055, which means that there is a significant effect so that partially there is an influence between job satisfaction (X1) on employee performance (Y).